2010
DOI: 10.1007/s12039-010-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of solid state phase transformations: Measurement and modelling of some basic issues

Abstract: A brief review of the issues involved in modelling of the solid state transformation kinetics is presented. The fact that apart from the standard thermodynamic parameters, certain path variables like heating or cooling rate can also exert a crucial influence on the kinetic outcome is stressed. The kinetic specialties that are intrinsic to phase changes proceeding under varying thermal history are enumerated. A simple and general modelling methodology for understanding the kinetics of non-isothermal transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Thus, the first detectable phase formation occurs not at the thermodynamic equilibrium temperature T o , but at a slightly higher temperature, that is decided by τ and β . In the real case, T ( β ) could be nonlinear, as τ ( T ) is itself is a function of T and β . However for the present study, the linear approximation is found to be applicable, as it is supported by the experimental data (see Figure ).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Thus, the first detectable phase formation occurs not at the thermodynamic equilibrium temperature T o , but at a slightly higher temperature, that is decided by τ and β . In the real case, T ( β ) could be nonlinear, as τ ( T ) is itself is a function of T and β . However for the present study, the linear approximation is found to be applicable, as it is supported by the experimental data (see Figure ).…”
Section: Discussionsupporting
confidence: 53%
“…In the real case, T(b) could be nonlinear, as t(T) is itself is a function of T and b. [102] However for the present study, the linear approximation is found to be applicable, as it is supported by the experimental data (see Figure 5). The incubation time is a measure of the compromise between thermodynamic driving force and kinetic mobility factor.…”
Section: Heating Rate Sensitivity Of Recrystallization Temperaturesupporting
confidence: 51%
See 2 more Smart Citations
“…As a result, new strongly magnetic minerals are created during heatingcooling experiments and mono-phase reactions and transitions are modified (Hanesch et al, 2006). Kinetics of these nonisothermal solid phase transformations strongly depend on the heating and cooling rates applied (Raju and Mohandas, 2010).…”
Section: Discussion Thermomagnetic Analysis Of Magnetic Susceptibilitmentioning
confidence: 99%